Épocas de consórcio de alho com beterraba perante três manejos do mato sobre a produtividade e o lucro - Mueller, Siegfried (1998)
The research was carried out with intercropped cultivation of garlic and beet, in Caçador, SC, Brazil. Four seeding epochs for beet (0, 15, 30 and 45 days after garlic planting) and three management systems for weeds (with herbicides, without control and with frequent weeding) were tested. It was hoped to determine the effects of this intercropping, in time and space, seeking the benefits in .weed control, efficient land use, productivity, commercial quality, and profitability. The randomized block design was in split-plots. The epochs represented the plots, and the management, the subplots, with four replicates. Napromide at 750 g/ha did not cause symptoms of intoxication in the garlic plants, nor in the beet. All the treatments in epochs at the initiation of intercropping, in three management systems for weeds, presented efficient land use values greater than 1. The profitability of the intercropping of garlic and beet only became evident in the management involving frequent weeding; in all epochs, profits were greater than for the respective epochs of monoculture of beet and monoculture of garlic.